Eficacia de los derechos humanos en México vía control internacional / Human Rights Efficiency in Mexico by Means of International Control Mechanisms - Torres Sandoval, Joshua Norberto; Camarillo Govea, Laura Alicia; Yáñez Núñez, Lorena Esmeralda (República y Derecho, 2017)
En este trabajo se destaca la trascendencia del control internacional que incide enla eficacia de los derechos humanos en México. Para tal valoración se recogen e identifican los ítems donde se observan transformaciones en el ámbito jurídico mexicano que dan cuenta de ello, detonados a partir de la reforma constitucional mexicana de 2011 que otorgó primacía a los tratados internacionales en materia de derechos humanos. El control internacional que se destaca es el que ejerce la Corte Interamericana de Derechos Humanos. This paper highlights the importance of international control that affects the effectiveness of human rights in Mexico. Based on the situation prevailing in Mexico prior to the 2011 reform in contrast to the situation proposed by the constitutional reform, generating high expectations regarding the way in which human rights would be recognized, protected, respected and guaranteed; And the role of international control through international bodies to achieve the effectiveness of human rights.